Non-ergodicity and PEER's framework formula. - Der Kiureghian, Armen (Earthquake engineering & structural dynamics.)
A framework formula for performance-based earthquake engineering, advocated and used by researchers at the Pacific Earthquake Research (PEER) Center, is closely examined. The formula was originally intended for computing the mean annual rate of a performance measure exceeding a specified threshold. However, it has also been used for computing the probability that a performance measure will exceed a specified threshold during a given period of time. It is shown that the use of the formula to compute such probabilities could lead to errors when non-ergodic variables (aleatory or epistemic)are present. Assuming a Poisson model for the occurrence of earthquakes in time, an exact expression is derived for the probability distribution of the maximum of a performance measure over a given period of time, properly accounting for non-ergodic uncertainties. This result is used to assess the approximation involved in the PEER formula for computing probabilities. It is found that the PEER approximation of the probability has a negligible error for probabilities less than about 0.01. For larger probabilities, the error depends on the magnitude of non-ergodic uncertainties and the duration of time considered and can be as much as 20 percent for probabilities around 0.05 and 30 percent for probabilities around 0.10. The error is always on the conservative side.